Disposition kinetics of ampicillin in White Leghorn hens - ALAM, M; BANERJEE, N C; YADAVA, K P (The Indian Journal of Animal Sciences, 2013)
The pharmacokinetics and tissue disposition of ampicillin after single i.v. dose (50 mg/kg bw) was studied in 2 groups of White Leghorn (WLH) hens. The plasma concentration ranged from 0.14±0.008 to 18.95±1.63 pg/ml for 12 hr. The mean values of phramacokinetic parametres for 11/2 Alpha, Beta Vd,CLB and T/P ratio were 0.44±0.02 hr, 2.66±0.11 hr, 7.17±0.80 litre/kg, 30.50±2.38 ml/kg/min and 2.61±0.19 respectively. The mean value of K12,K 21, K10, and K12/K21 was 0.43±0.04 hr-1 ,0.43±0.03 hr -1,0.95±0.03 hr-1 and 1.01-+iD.05 hr respectively. The level of drug in hile was 3S.99±1.81 alphag/ml and 37.17±2.34 pg/ml at 4 and 24 hrpost-dmg administration respectively. Ampicillin residual level was determined in different organs and skeletal muscles of the birds at 4 and 24 hr post-administration. Dosage regimen based on the kinetics of drug has been suggested for optimal clinical efficacy.